О некоторых выразительных средствах рекламной коммуникации (на материале словацкой коммерческой рекламы) - Gallo, Jan; Miliaev, Fedor (Studia Rossica Posnaniensia, 2026)
The paper focuses on the linguistic expressive means of Slovak commercial advertising, manifested at the lexical and syntactic levels. The intertextual and interdiscursive means of commercial advertising, as well as some techniques of argumentation in advertising, are presented as well. An analysis of advertising slogans and texts revealed that the arsenal of devices that make up the language of Slovak commercial advertising is quite extensive. The most typical lexical and syntactic devices in Slovak commercial advertising include pseudo-terms, evaluative vocabulary, superlatives, familiar diminutives, fashionable words, neologisms, juxtaposition, sequential parcellation of utterances, syntactic parallelism, beneficiary constructions, and adverbial clauses of cause and purpose. The most typical intertextual and interdiscursive means of Slovak commercial advertising include quotations that refer to cultural realities (stereotypes) that are understandable to an average recipient, the actualization of a well-known expression, a constant epithet, and the phenomenon of an advertising campaign. Argumentation in Slovak commercial advertising is represented by a direct call to purchase a product or service (called a “hard sell”), strategies of persuasion and seduction, and a combination of these. An analysis of Slovak commercial advertising revealed a fairly wide variety of expressive means and confirmed its communicative-pragmatic focus with a predominantly persuasive function (the primary goal of advertising texts is to convince the recipient of the need to purchase the product). This particular characteristic of commercial advertising determines the choice of linguistic (syntactic, lexical, etc.) means that enhance the impact on the recipient’s mental sphere.